Intestinal transplantation in children with multiple intestinal atresias and immunodeficiency. (28th December 2013) - Fischer, Ryan T.; Friend, Brian; Talmon, Geoffrey A.; Grant, Wendy J.; Quiros‐Tejeira, Ruben E.; Langnas, Alan N.; Coccia, Peter F.
Abstract GVHD has been reported in 8–10% of children after small bowel transplant (SBTx). Immunodeficient children may be predisposed to aggressive, steroid‐resistant GVHD. There exists a unique association of immunodeficiency in children with MIA (MIAI). We report on our SBTx experience in patients with the diagnosis of MIAI, their high incidence of GVHD, and the possible role of stem cell transplantation in these patients. We performed a review of records from children that underwent SBTx or that we evaluated for SBTx at our institution. We focused on the diagnoses of atresia, multiple intestinal atresia, immunodeficiency, and GVHD in our patient population. Children with MIAI are likely to experience severe GVHD following SBTx. MIAI correlated with a 100% incidence of GVHD in these patients. Of the five patients with MIAI that underwent SBTx, three succumbed to severe GVHD within 1–6 months after SBTx. One patient received stem cell transplant prior to SBTx and did not develop severe GVHD, but died from influenza nine months after SBTx. Our unique patient survives long‐term, with engraftment of donor γ δ T cells. He has mild, persistent chronic GVHD. Atresia is a common referral diagnosis for SBTx. Patients with multiple atresias, especially MIAI, are at significant risk for the complication of GVHD following SBTx. We recommend careful immunologic assessment and antecedent stem cell transplant in children with MIAI prior to SBTx.